PERANCANGAN DAN PENETAPAN STANDAR PELAYANAN PADA KANTOR KELURAHAN WALA-WALAYA KECAMATAN TALLO KOTA MAKASSAR - Hikmah S., Nur; Fransisca Tonapa, Jessica (Politeknik STIA LAN Makassar, 2024)
At the Wala-Walaya Village Office, Tallo District, Makassar City, there have been no Service Standards as guidelines for providing services to the community. Government executors are obliged to provide service standards to guarantee quality, affordable and measurable services as a mesurement of government performance to create quality services for the community. Through the preparation and establihsment of Service Standards for the three types of service standards that are most frequently requested by peolpe who come to the Wala-Walaya Village Office, as form of guarantee in providing services to the community and improving service quality. This research is a descriptive study using a qualitative approach. The data in this research were obtained from interviews with Wala-Walaya Village Office employees and the local community, direct observations regarding service delivery and document review. The results of this research are 3 Service Standard documents provides at the Wala-Walaya Village office, Tallo District, Makassar City. The Service Standard Document is for the type of Resident Card Cover Letter (KTP) service, Family Card Cover Letter (KK) service, and Domicile Certificate Cover Letter service.